Grip strength comparison in immune‐mediated neuropathies: Vigorimeter vs. Jamar. Issue 3 (September 2015) - Draak, Thomas H. P.; Pruppers, Mariëlle H. J.; van Nes, Sonja I.; Vanhoutte, Els K.; Bakkers, Mayienne; Gorson, Kenneth C.; Van der Pol, W.‐Ludo; Lewis, Richard. A.; Notermans, Nicolette C.; Nobile‐Orazio, Eduardo; Léger, Jean‐Marc; Van den Bergh, Peter Y. K.; et al.
Abstract The Jamar dynamometer and Vigorimeter have been used to assess grip strength in immune‐mediated neuropathies, but have never been compared to each other. Therefore, we performed a comparison study between these two devices in patients with immune‐mediated neuropathies. Grip strength data were collected in 102 cross‐sectional stable and 163 longitudinal (new diagnoses or changing condition) patients with Guillain‐Barré syndrome (GBS), chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), gammopathy‐related polyneuropathy (MGUSP), and multifocal motor neuropathy (MMN). Stable patients were assessed twice (validity/reliability studies). Longitudinal patients were assessed 3‐5 times during 1 year. Responsiveness comparison between the two tools was examined using combined anchor‐/distribution‐based minimum clinically important difference (MCID) techniques. Patients were asked to indicate their preference for the Jamar or Vigorimeter. Both tools correlated highly with each other (ρ = 0.86, p < 0.0001) and showed good intra‐class correlation coefficients (Jamar [Right/Left hands]: ICC 0.997/0.96; Vigori: ICC 0.95/0.98). Meaningful changes were comparable between the two instruments, being higher in GBS compared to CIDP patients. In MGUSP/MMN poor responsiveness was seen. Significant more patients preferred the Vigorimeter. In conclusion, validity, reliability, and responsiveness aspects were comparable between the Jamar dynamometer and Vigorimeter. However, based on patients' preference, the Vigorimeter is recommended in future studies in immune‐mediated neuropathies.